Clinical Impact of SPECT/CT in Evaluation of Abdominothoracic Fistula. (20th April 2023) - Kang, Seo Young; Moon, Byung Seok; Yoo, Min Young; Yoon, Hai-Jeon; Kim, Bom Sahn
Abstract: Abdominothoracic fistula is rarely observed but can be life-threatening. Pleuroperitoneal communication, known to occur in 1.6% of all patients who undergo continuous ambulatory peritoneal dialysis, is an uncommon but well-recognized complication. The most common symptoms are dyspnea and right-sided pleural effusion. A biliopleural fistula is well-described as a complication of radiofrequency ablation and transcatheter arterial chemoembolization of hepatic lesions. It is important to diagnose the cause of pleural effusion early for proper treatment because if the abdominothoracic fistula effusion amount is not large, appropriate diagnosis may be difficult. Here, we introduce 2 cases showing the usefulness of SPECT/CT in evaluating pleuroperitoneal and biliopleural fistulas.